A cross‐sectional study evaluating the frequency of HIV drug resistance mutations among individuals diagnosed with HIV‐1 in tenofovir disoproxil fumarate‐based pre‐exposure prophylaxis rollout programmes in Kenya, Zimbabwe, Eswatini and South Africa - Urvi M. Parikh; Lauren D. Kudrick; Lisa Levy; Everline Bosek; Bhavna H. Chohan; Irene Mukui; Sarah Masyuko; Nonhlanhla Ndlovu; Imelda Mahaka; Owen Mugurungi; Gertrude Ncube; Anita Hettema; et al. (Journal of the International AIDS Society)
Abstract Introduction The ongoing rollout of oral tenofovir‐based pre‐exposure prophylaxis (PrEP) has the potential to reduce HIV‐1 incidence, but HIV drug resistance (HIVDR) in individuals who acquire HIV‐1 on PrEP could threaten the treatment effectiveness of overlapping antiretrovirals (tenofovir/emtricitabine), contribute to development of resistance, and undermine HIV control efforts. Accordingly, the Global Evaluation of Microbicide Sensitivity (GEMS) project was established to monitor HIVDR in PrEP rollout programmes in Southern and Eastern Africa. Methods GEMS monitored resistance in >100,000 estimated persons who accessed PrEP through national programmes or implementation projects in Southern/Eastern Africa. Participants self‐reported demographics and PrEP adherence. HIV‐1 RNA and tenofovir‐diphosphate levels were measured in blood samples collected at the time of study enrolment from consenting participants diagnosed with HIV who had received PrEP. HIVDR mutations were detected by population genotyping. Results Of 283 reported seroconversions on PrEP from December 2017 through September 2023, 255 (90%) individuals enrolled in GEMS, of which 81 (32%) were from Kenya, 77 (30%) from South Africa, 69 (27%) from Zimbabwe and 28 (11%) from Eswatini. Half (130; 51%) were 15–24 years of age at seroconversion, and three‐quarters (193; 76%) were female. Thirty‐four seroconversions occurred within 30 days of PrEP initiation. Tenofovir‐diphosphate levels were consistent with moderate to high levels (≥350 femtomoles per punch) in 53% (120 of 226) individuals with drug‐level data. Of 154 samples successfully genotyped, 34 (22%; 95% CI [16%, 30%]) had PrEP‐associated mutations; these included 27 samples with M184I/V, one sample with K65KR, and six samples with both K65R and M184I/V. Conclusions The frequency of HIVDR mutations associated with tenofovir or emtricitabine among individuals diagnosed with HIV who had received PrEP (22%) exceeded background levels of transmitted nucleoside reverse transcriptase inhibitor resistance in Southern and Eastern Africa (≤5%) but people with PrEP‐associated mutations are likely to achieve virologic suppression with current first‐line antiretroviral therapy (ART). Improved screening for acute infection before initiating PrEP, surveillance of HIVDR with the introduction of new PrEP programmes and the monitoring of longer‐term ART outcomes in individuals who acquire HIV‐1 on PrEP will be essential to preserve antiretroviral options for both treatment and prevention.